Publishing Economics: How Slow? Why Slow? Is Slow Productive? Fixing Slow? - Aboozar Hadavand; Daniel S. Hamermesh; Wesley W. Wilson (Institute of Labor Economics (IZA), 2021)
Publishing in economics proceeds much more slowly on average than in the natural sciences, and more slowly than in other social sciences and finance. It is even relatively slower at the extremes. We demonstrate that much of the lag, especially at the extremes, arises from authors' dilatory behavior in revising their work. The marginal product of an additional round of re-submission at the top economics journals is productive of additional subsequent citations; but conditional on re-submission, journals taking more time is not productive, and authors spending more time is associated with reduced scholarly impact. We offer several proposals to speed up the publication process. These include no-revisions policies, such as Economic Inquiry's; limits on authors' time revising articles, and limits on editors waiting for dilatory referees.
Keywords: A11; B20; 330; procrastination; top journals; sociology of economics; slowness; editorial behavior